Cascading principles expansions within geometry, philosophy, and interference - Üstek, Fatoş 1980- (Mousse Publishing, 2024)
Cascading Principles. Expansions Within Geometry, Philosophy, and Interference is an Archivorum×M artist’s book, a publishing series conceived for Magic Megève. The publication was released to accompany Conrad Shawcross’s largest UK survey exhibition to date, the first held at the Mathematical Institute in Oxford. Four lectures were held as part of the exhibition, all aimed at fostering cross-disciplinary knowledge production in fields such as mathematics, quantum physics, philosophy, and art. The publication includes transcriptions and special contributions from all speakers, exhibition installation images, and an essay by the curator, Fatoş Üstek
Published on the occasion of Conrad Shawcross' major UK survey exhibition, curated by Fatoş Üstek at the Mathematical Institute, Oxford University, which opened in September 2022. - Genaue Ausstellungsdaten ermittelt: 28 Sep 2022 - 30 Jun 2025
Edited by Fatoş Üstek, texts by Martin Bridson, Chrystal Cherniwchan, Jon Keating, Maya B. Kronic, Liliane Lijn, Sir Roger Penrose, Emma Ridgway, Carlo Rovelli, Marcus du Sautoy, and James Sparks
Keywords: Shawcross, Conrad -- 1977-; Ausstellungskatalog -- Oxford University, Mathematical Institute -- 28.09.2022-30.06.2025 -- Oxford